Gender Differences in Patterns of Substance Use and Delinquency: A Latent Transition Analysis. Issue 2 (4th March 2017) - Bright, Charlotte Lyn; Sacco, Paul; Kolivoski, Karen M.; Stapleton, Laura M.; Jun, Hyun-Jin; Morris-Compton, Darnell
Abstract: This study explores gender-specific patterns and transitions of adolescent substance use and delinquency in a sample of youths at ages 12, 15, and 18 ( N = 803). Latent transition analysis identified "Primary Delinquent, " "Delinquency and Substance Use, " and "Low Risk" classes. Females were less likely to be in the "Primary Delinquent" class at age 12 than males. From 15 to 18, females were approximately equally likely to transition from "Primary Delinquent" to both other classes, whereas males were more likely to transition from "Primary Delinquent" to "Delinquency and Substance Use." These gender differences in behavior can inform services.